2020
DOI: 10.1590/1518-8345.4675.3383
|View full text |Cite
|
Sign up to set email alerts
|

Elderly individuals living by themselves: knowledge and measures to prevent the novel coronavirus

Abstract: Objective: to describe the occurrence of COVID-19 and the health services used by elderly individuals living by themselves; identify the knowledge held by elderly individuals regarding the transmission, signs and symptoms of COVID-19, as well as factors associated with poor knowledge of preventive measures according to sociodemographic and clinical variables. Method: cross-sectional survey conducted by telephone or mobile with 123 elderly individuals living by themselves in the Health Macro-Region of Triângul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 37 publications
(110 reference statements)
1
9
0
3
Order By: Relevance
“…In fact, risk perception can be influenced by several aspects, including knowledge of the virus [ 44 ] and the socio-economic status. Previous studies [ 45 , 46 ] have shown that older, socio-economically disadvantaged, and poorly-educated individuals are less informed about COVID-19 spreading and, therefore, do not take adequate precautions.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, risk perception can be influenced by several aspects, including knowledge of the virus [ 44 ] and the socio-economic status. Previous studies [ 45 , 46 ] have shown that older, socio-economically disadvantaged, and poorly-educated individuals are less informed about COVID-19 spreading and, therefore, do not take adequate precautions.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of knowledge regarding RI prevention results in impacts on individuals' health, increasing the risk of transmission of pathogens that cause these infections (10) . It emphasizes the need to measure knowledge in order to direct actions to increase it and, consequently, promote changes in beliefs and behaviors (40) . However, it cannot be guaranteed that knowledge about preventive measures will lead to proper practice.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study to investigate knowledge about COVID-19 in the general Brazilian population. Other studies have been conducted with specific segments, such as the elderly, diabetics, or dental health professionals [ 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%